Diallyl trisulfide induces apoptosis in Jurkat cells by the modification of cysteine residues in thioredoxin. Issue 8 (3rd August 2014) - Watanabe, Kazunari; Hosono, Takashi; Watanabe, Kazuhiro; Hosono-Fukao, Tomomi; Ariga, Toyohiko; Seki, Taiichiro
Abstract: We reported the regulation of protein function by oxidative modification of the specific cysteine residue(s) by diallyl trisulfide (DATS). In this study, we examined if DATS modifies the cysteine residue of thioredoxin (Trx) by urea-polyacryl amide gel electrophoresis. DATS modified two specific cysteine residues in Trx and this oxidative modification of cysteine residues would be sole causative of the apoptosis induced by DATS in leukemic cells.